Effects Of Different Processes On Mechanical Properties Of CFRP By RTM And VIP Techniques - Yaakob, Mohd Yuhazri; Husin, Mohd Amirhafizan; Abdullah, Zailinda; H., Sihombing; S.T.W., Lau (2019)
There is a high demand of hinge bracket for aircraft spoilers from metallic to composite materials in aircraft industries. Therefore, new fabrications process studies to replace the current process. Moreover, the current fabrication processes are of tooling and production are expensive as well as high testing cost. Thus, studies present the effect of different number and orientation of woven carbon fiber layers in laminated composites (CFRP) system in mechanical properties. The composites were fabricated based on eight plies, 16 plies, 24 piles and 32 plies of woven carbon fiber layers. The same orientation of woven carbon fiber layer was fabricated using two different processes which are Resin Transfer Moulding Process (RTM) and Vacuum Infusion Process (VIP). The composites fabricated using both processes undergo tensile test and flexural test to evaluate the effect of different process fabricating the composites with a different number of woven carbon fiber layers. Based on the results, the best properties of composites based on the different fabricated process and number of woven carbon fiber layers can be proposed to replace the manufacturing process for hinge bracket for aircraft spoilers were obtained. The result from the experiment shows that 8CF/EP composites fabricated using VIP have 10.6 % higher in specific strength obtained from tensile test and 64.4 % higher in specific strength obtained from the flexural test. From this results of this study indicate that the composites with 8 plies of carbon fiber fabricated using VIP has a good tensile and flexural strength compared to composites fabricated using RTM and other different plies of carbon in the composite.